NLRP3 inflammasome is expressed by astrocytes in the SOD1 mouse model of ALS and in human sporadic ALS patients. Issue 12 (21st July 2015) - Johann, Sonja; Heitzer, Marius; Kanagaratnam, Mithila; Goswami, Anand; Rizo, Tania; Weis, Joachim; Troost, Dirk; Beyer, Cordian
<x xml:space="preserve">Abstract</x> Amyotrophic lateral sclerosis (ALS) is characterized by the degeneration of motoneurons in the cerebral cortex, brainstem and spinal cord. Neuroinflammation plays an important role in the pathogenesis of ALS and involves the activation of microglia and astrocytes. Intracellular inflammasome complexes are part of the innate immunity as they sense and execute host inflammatory responses. The best characterized component is the NLRP3 inflammasome comprised of the NLR protein NLRP3, the adaptor ASC and pro‐caspase 1. The NLRP3 inflammasome is critical for the activation of caspase 1 and the processing and release of IL1β and IL18. In this study, we investigated the expression, activation and co‐localization of the NLRP3 inflammasome in the spinal cord of male SOD1(G93A) mice carrying a mutant human superoxide dismutase 1 (SOD1) variant and regarded as an animal model for ALS as well as in post‐mortem tissue of ALS patients. NLRP3 and its molecular components as well as IL1β were already detectable in SOD1 mice at a pre‐symptomatic stage after 9 weeks and further increased in 14 week old animals. Spinal cord astrocytes were identified as the major cell type expressing NLRP3 components. In human ALS tissue, we also found increased NLRP3, ASC, IL18 and active caspase 1 levels compared to control patients. Our findings suggest that astroglial NLRP3 inflammasome complexes are critically involved in neuroinflammation in ALS. GLIA 2015;63:2260–2273